PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN PERAN KOMITE SEKOLAH TERHADAP KEBERHASILAN MANAJEMEN BERBASIS SEKOLAH - Seriyanti, Nela; Ahmad, Syarwani; Destiniar, Destiniar (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
This study determined the effect of Principal’s leadership and the Role of School Committee for the Success of School Based Management at Senior High School Negeri 1 Sirah Pulau Padang. This study used quantitative methods. Data were analyzed using multiple linear regression partial correlation and multiple correlation.This study showed that; 1) there is significant influence between principal's leadership on school-based management at SMA Negeri 1 Sirah Pulau Padang; 2) there is significant influence between the role of the school committee on school-based management at SMA Negeri 1 Sirah Pulau Padang. 3) there is simultaneously influence among Principal’s leadership and the Role of School Committee for the Success of School Based Management at Senior High School Negeri 1 Sirah Pulau Padang. The implication of the research is that the Principal’s leadership and the Role of School Committee for the Success of School must be considered in improving school-based management so that the educational goals will be optimal.